PENGEMBANGAN PETA POTENSI DESA BERBASIS SPASIAL UNTUK MENDUKUNG PERENCANAAN PEMBANGUNAN DESA DI KECAMATAN BUNGA RAYA KABUPATEN SIAK - Suwondo Suwondo; Almasdi Syahza; Musrifin Galib; Reby Oktarianda (Jurnal Hilirisasi IPTEKS, 2020)
Village development planning requires information in the form of spatial data that is precise and accurate so that it can be used to analyze development needs in environmental, economic, and social aspects. It shows the limited spatial information related to village administration, village potential, and toponymy. The development of a spatial-based village potential map aims to present spatial information to be used in village development planning. The spatial map was developed through a participatory approach by involving Riau University students. Data collection was carried out with multi parties' participation, including the Geospatial Information Agency, Siak Regency Government, LPPM Riau University, and the World Research Institute. The method of developing spatial maps is done using the Avenza Maps application based on android and Arc Gis. The activity was carried out in Bunga Raya District, Siak Regency. Development activities are carried out through the stages of preparation (identification of needs and training), implementation (field mapping), and evaluation (making village spatial maps and verification). The results of developing a spatial-based village potential map showed promising results. The preparation stage resulted in identifying the components needed, such as base maps, developing student human resources by conducting training on using the Avenza Maps application. The implementation stage produces spatial coordinates of the village potential through participatory field surveys between Riau University students and the District's community/village apparatus. The evaluation stage produces spatial maps that have been verified by the Siak Regency Government, especially the village administrative boundaries. Thus, spatial mapping results can be used as a database in development planning and can be used as a baseline for spatial data for Siak Regency.